PENGARUH CROSSBREED TERHADAP PERFORMA REPRODUKSI SAPI POTONG DI KABUPATEN SLEMAN DAN KABUPATEN BANTUL - , VANIA DINARESTY ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Crossbreeding is an attempt to improve the genetic quality of Indonesian local cattle. The majority of Indonesian people prefer crossbreed cattle because of its good quality calf. However the data regarding to the reproduction performance of crossbreed cattle are rare. The purpose of this research was to know about the comparison of crossbreed cattle and Indonesian local cattle, specifically Peranakan Ongole (PO) cattle, in Sleman and Bantul livestock groups. The observation variables were Service per Conception (S/C), Calving Interval (CI) and Estrous Post Partum (EPP). The acquired samples were 22 heads of Crossbreed cattle and 6 heads of PO cattle. The research was utilized by using survey method, specifically questionnaire and interview. Then, the survey result was processed further by using independent t-test. The research result showed that S/C, CI, and EPP of crossbreed cattle in succession are 2,45 ± 0,80, 14,41 ± 2,65, and 81,82 ± 31,11, whereas PO cattle in succession are 2,67 ± 0,82, 18,50 ± 3,08, and 102,5 ± 30,62. The conclusion of this research are crossbreed cattle and local cattle showed a significant difference, but S/C and EPP did not showed a significant difference.